Kepercayaan Tolotang dalam Perspektif Masyarakat Bugis Sidrap - Syukur, Nur Ahsan (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The research aims to describe Tolotang’s belief which locates in Sidenreng Rappang (Sidrap Region). According to the result of this research was known that the belief of Tolotang had existed since the era of their ancestor until now. The existence of Tolotang proves that a whole of Sidrap society believes Tolotang as a cultural religion or ancient religion. The development of Tolotang on a high scale made a debate among Sidrap Buginese Society and Indonesia Government. It can be seen by society arguments that Tolotang is a local wisdoms or local culture. In the other side, the government says that this religion will wreck the order of recognized religions in this area.